2017
DOI: 10.3732/ajb.1700163
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution and niche differentiation within the common peatmossSphagnum magellanicum

Abstract: We show that the two morphs represent the two main genetic clusters previously found worldwide. Our results demonstrate that relatively minor morphological differentiation in a presumed phenotypically plastic peatmoss may be associated with massive divergence across the genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 90 publications
1
22
0
4
Order By: Relevance
“…Contrary to our predictions, our results showed that the hummock plants had 369 relatively lower F v /F m across all experimental treatments compared with the hollow plants. Also,370 under the shade treatments, some of the hummock plants changed from reddish to light pink 371 colour and some with a tint of green, which is consistent with the findings that pigmentation of S. 372 magellanicum is plastic (Yousefi et al, 2017). This means that the pigmentation is induced by 373 the environment.…”
Section: Light Controls On Sphagnum Trait Variation 356supporting
confidence: 75%
See 1 more Smart Citation
“…Contrary to our predictions, our results showed that the hummock plants had 369 relatively lower F v /F m across all experimental treatments compared with the hollow plants. Also,370 under the shade treatments, some of the hummock plants changed from reddish to light pink 371 colour and some with a tint of green, which is consistent with the findings that pigmentation of S. 372 magellanicum is plastic (Yousefi et al, 2017). This means that the pigmentation is induced by 373 the environment.…”
Section: Light Controls On Sphagnum Trait Variation 356supporting
confidence: 75%
“…The preliminary 429 study suggests that S. medium has an amphi-Atlantic distribution while S. divinum is circumpolar 430 in its distribution. Since the pigmentation of "S. magellanicum" (as we currently know it) lacks 431 genetic basis (Yousefi et al, 2017) and considering the pattern of distribution of these species 432 relative to our field site in Southern Ontario, it is unlikely that we sampled across a mix of S. 433 medium and S. divinum in a way that would bias our findings. Also, considering that origin had 434 little effect on trait variability, a more likely scenario is that we sampled one species or the other.…”
Section: Implications Of Trait Variability and Local Adaptation In Spmentioning
confidence: 99%
“…An additional factor that cannot be discounted is that variation observed under controlled growth conditions would not be expressed in the field, due to G × E. Our data show a high proportion of characters clearly influenced by this interaction. Some studies performed a reciprocal transplant experiment (Såstad, 1999;Såstad & al., 1999;Hassel & al., 2005;Yousefi & al., 2017) to advise on the adaptive capacity of morphological characters. Ecological gradients have been studied extensively in Sphagnum L. species from the same natural area, where variations in pH or water level are easily observable (Såstad, 1999;Såstad & al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic variation within species may be caused by genotypic differences (Såstad & al., 1999;Savolainen & al., 2013) or by differential gene expression induced by environmental variability (Price & al., 2003;Pigliucci & al., 2006). Assessing the adaptive significance of morphological trait variation is a fundamental issue in evolutionary ecology (Såstad & al., 1999;Yousefi & al., 2017) and in systematics (Shaw & Bartow, 1992;Såstad, 1999), avoiding the overestimation of biodiversity. On the other hand, relying on morphological methods alone may miss cryptic species and therefore underestimate species diversity (Bickford & al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation